Early Childhood Teacher Teaching Profile: Teaching Creatively or Teaching for Creativity - Akhmad Mukhlis; Sofia Amalia (UPI Kampus Cibiru, 2023)
Teaching creatively and teaching for creativity are two critical things in implementing the concept of teaching creativity. This study aims to find out whether teachers tend to teach creatively or teach for creativity. A quantitative approach using the survey method was chosen to see trends in the teaching abilities of early childhood teachers. Seventy-six teachers of Early Childhood Education (PAUD) in Malang City participated in this study. Quantitative data were processed using non-parametric statistics, the Wilcoxon test. The findings in the study show that teachers are more likely to teach creatively than teach for creativity, although, in general, the teachers in this study also have high scores in teaching for creativity. The main obstacle for teachers in implementing a teaching for creativity is the ability to identify creative students, encourage creativity and facilitate student creativity. Additional policies are needed to facilitate teacher teaching for creativity, especially in identifying, encouraging, and facilitating student creativity.